Identification of new therapeutic compounds against carbapenemase-producing Klebsiella pneumoniae using a novel agar-based high-throughput microarray compound screening approach - Mahlangu, Zandile (Department of Chemistry, 2024)
Klebsiella pneumoniae, a Gram-negative bacterium, is a common cause of hospital-acquired pneumonia, urinary tract infections (UTIs), bacteraemia, septicaemia, and wound/surgical site infections. Over the years, the pathogen developed resistance to most β-lactam antibacterial drugs used in clinical care. The most important of these drugs are carbapenems – a class of broad-spectrum antibiotics reserved for the treatment of infections caused by multidrug-resistant (MDR) bacteria. The emergence of carbapenem resistance has resulted in limited or ineffective treatment options for MDR K. pneumoniae. This prompted a global initiative to prioritize this pathogen for new drug discovery and development to reduce the severity of such infections. Therefore, this study aimed to develop a cost-effective high-throughput antibacterial microarray screening platform to accelerate drug screening efforts against carbapenemresistant K. pneumoniae. To achieve this, an agar-based microarray assay, modeled based on the standard disc diffusion assay, was developed by optimizing the assay parameters, including the cellulose nanofiber (CNF) immobilization matrix, polymer component of the printing solution, inoculum, agar thickness, and agar concentration. The optimized parameters for effectively running the high-throughput antibacterial screen were set at 1.5% (w/v) CNF immobilization matrix into which spots were printed, 1.6% hydroxypropyl methylcellulose printing solution – serving as a binding agent for compounds, inoculum density ranging between ~1 x 105 and 2 x 105 CFU/mL, 0.8% (w/v) seeding agar which formed a ~0.4 mm layer into which printed compounds diffused into and affected bacteria, and 1.5% (w/v) plain agar which formed a ~1.6 mm layer overlaying the thin seeded agar layer. A proof-of-concept of the developed assay was demonstrated by screening a panel of 12 FDA-approved antibacterial drugs against five bacterial strains with varying degrees of drug susceptibility (i.e., K. pneumoniae 1705, K. pneumoniae 700603, K. pneumoniae 33495, Staphylococcus aureus 25923, and Escherichia coli 25922). Varying patterns and levels of bacterial susceptibility were observed on the platform, with three (polymyxin B sulfate, colistin sulfate, and gentamicin sulfate) and two (polymyxin B sulfate and colistin sulfate) test drugs showing antibacterial activity against K. pneumoniae 1705 and 700603, respectively. Drugsusceptible K. pneumoniae 33495, E. coli 25922, and S. aureus 25923 exhibited susceptibilities to six (polymyxin B sulfate, colistin sulfate, gentamicin sulfate, kanamycin sulphate, G418 sulfate, and tobramycin), seven (polymyxin B sulfate, colistin sulfate, gentamicin sulfate, kanamycin sulphate, G418 sulfate, tobramycin, neomycin sulfate), and five (kanamycin sulphate, neomycin sulfate, gentamicin sulfate, G418 sulfate, tobramycin) drugs, respectively. The optimised assay was used to screen a diverse library of 4154 compounds against a carbapenem-resistant K. pneumoniae (ATCC BAA 1705) and a drug-susceptible K. pneumoniae (ATCC 33495) strains. The primary screen data was mined for antibacterial hits using an assay specific two-step data analysis method (i.e., combination of Z-score data analysis method and image-based analysis). The screening did not yield hits against the carbapenemresistant K. pneumoniae. A secondary screen of 5% of inactive compounds, with Z-scores ranging between standard deviations (SD) of -1 and -2, selected from the primary screen against K. pneumoniae 1705 and 33495, was conducted to test the accuracy and reliability the of the two-step data analysis method and the hit selection criteria. A percentage agreement of >99% was obtained between the results obtained in the primary screen (using the agar-based microarray assay) and those obtained in the secondary screen (using the broth microdilution assay). The developed assay showed great potential as a rapid primary screening tool for anti-K. pneumoniae compounds.